The Effect of a VAT Rate Reduction on Enterprise Costs: Empirical Research Based on China’s VAT Reform Practice - Liu, Yongjiu; Wang, Wei; Liu, Chao (Frontiers in Environmental Science, 2022)
China has implemented a series of tax system reforms to improve the business environment, reduce the burden on enterprises and promote supply-side structural reform. In this article, we focus on the value-added tax (VAT) rate reduction that occurred in 2018 and 2019. We analyse the mechanism of the impact of the VAT rate reduction on enterprises' costs and conduct an empirical test using the DID model and data from Chinese listed companies. The main conclusions are as follows. First, the reduction of VAT rate can significantly reduce the total cost of enterprises. This means that the reduction of VAT rate plays a positive role in reducing enterprise burden, stimulating enterprise vitality and improving enterprise performance. Second, the "cost reduction" effect is more obvious in non-state-owned enterprises than state-owned enterprises. Third, Further heterogeneity analysis shows that the cost reduction effect is more obvious in enterprises that are high-cost, large scale, and those located in eastern China. Small and medium-sized enterprises and those found in the central and western regions failed to significantly reduce operating costs, indicating that they did not benefit fully from a reduced VAT rate, which partly shows that the benefits of VAT tax reduction are not evenly distributed among enterprises. This study can provide a reference for the government to further improve the tax system, optimize the living environment of enterprises, and promote the sustainable development of economy.